2000
DOI: 10.1055/s-2000-9005
|View full text |Cite
|
Sign up to set email alerts
|

Does Gastroscopy Induce Myocardial Ischemia in Patients With Coronary Heart Disease?

Abstract: Gastroscopy is potentially a harmful procedure for CHD patients, but the incidence of ischemic periods may be reduced by conscious sedation and, if the patient is receiving beta-blocking agent therapy, by applying this medication prior to gastroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Overall, conscious sedation is overwhelmingly safe, with a very low risk of death, requirement for artificial ventilation, myocardial infarction, or central nervous system damage. Therefore, hypoxemia is used as a surrogate for these outcomes due to rarity of these hard events and also because hypoxemia is a precursor to these outcomes [16][17][18][19]. As the majority of studies included heterogeneous patient groups, further risk factor assessment in these studies has been potentially confounded by the strong influence of ASA class.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, conscious sedation is overwhelmingly safe, with a very low risk of death, requirement for artificial ventilation, myocardial infarction, or central nervous system damage. Therefore, hypoxemia is used as a surrogate for these outcomes due to rarity of these hard events and also because hypoxemia is a precursor to these outcomes [16][17][18][19]. As the majority of studies included heterogeneous patient groups, further risk factor assessment in these studies has been potentially confounded by the strong influence of ASA class.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the symptoms of gastroduodenal dyspepsia, when specifically sought by a physician during structured interview with the patients, could identify the group of IHD patients with PUD prevalence of 37.5 %. A recent study by Schenck et al included 71 patients with IHD in whom gastroscopy was performed to assess the potentially harmful effects of the procedure in IHD patients [11]. Study results showed gastroscopy to be a safe procedure in patients with stable IHD, although they had a very high rate of silent myocardial ischemia during endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopy has been shown to induce cardiovascular complications, including myocardial ischemia [40,41,54]. Thus, this practice may serve as an additional explanation for the frequent diagnosis of cardiovascular disease in patients experiencing upper gastrointesti-nal symptoms.…”
Section: Overlapping Symptomatology and Surveillancementioning
confidence: 99%
“…However, more recent studies in patients with stable coronary disease or those at risk for cardiovascular disease have observed much higher rates of cardiovascular complications following endoscopy. In a study of 71 patients with stable coronary heart disease undergoing endoscopy for evaluation for the safety of secondary prophylaxis with aspirin, 42% of patients experienced silent ischemia and one patient had a symptomatic event [40]. A second study utilizing data from 9 hospitals in the United States evaluated 602 charts for patients undergoing endoscopy and deemed to be at risk for cardiovascular disease.…”
Section: Overlapping Symptomatology and Surveillancementioning
confidence: 99%
See 1 more Smart Citation